Coriander cultivation at farmers’ field for livelihood security - Singh, Sanjive Kumar; Rajiv, Rajiv; Singh, Senjum Jinus; Kashyap, Poonam (Indian Horticulture, 2019)
Coriander is a high-value crop. It can be cultivated round the year either in open fields or in protected conditions. Its cultivation in greenhouse fetches higher return in summer season. Though its cultivation is very remunerative most of the time, it needs proper attention and should be popularized as more income generating crop.